COMPARISON OF STRENGTHENING EXERCISE AND RANGE OF MOTION (ROM) TO DECREASE THE INTENSITY OF PAIN IN THE ELDERLY WITH OSTEOARTHRITIS IN SIMPANG TIGA PEKABARU HEALTH CENTER. (Al Insyirah International Scientific Conference on Health, 2021)
Osteoarthritis is a degenerative disease, which is experienced by elderly that characterized by pain in the lower extremities and its prevalence increases by getting older. Non-pharmacological management is a very important component to solved pain with Strengthening Exercise and Range of Motion (ROM) exercises. This study aims to determine the comparison of Strengthening Exercise and Range of Motion (ROM) to decrease the intensity of pain in the elderly with Osteoarthritis in Simpang Tiga Pekabaru Health Center. This type of quantitative research, quasy experiment design with pre-test and post-test design. The number of respondents was 28 people, Strengthening Exercise 14 people and Range of Mation (ROM) 14 people. This research used Purposive sampling technique. Data analysis by  dependent T-test and Independent T-test. The results showed that there was a significant comparison between Strengthening Exercise and Range of Mation (ROM) to decrease pain intensity with p
Keywords: Strengthening Exercise; Range Of Mation; Osteoarthritis; elderly